HISTORICAL AND MANAGEMENT ASPECTS OF VETERINARY MEDICINE DEVELOPMENT IN UKRAINIAN LANDS IN 11 TH – 17 TH CENTURIES - Didok Yu.V. (Pressing Problems of Public Administration, 2018)
The article is devoted to studying of historical and management aspects of the veterinary medicinedevelopment of Ukraine in the period of the 11TH – 17TH centuries. The features of public administrationand the state of veterinary medicine development in the territory of Ukrainian lands in the times ofKievan Rus, the Tatar-Mongol invasion, the Lithuanian and Polish domination and the Cossack erahave been characterized. The expedience of considering the said historical periods as a stage offorming prerequisites for the public administration in the  eld of veterinary medicine in Ukraine hasbeen substantiated. Historical achievements of this historical period in terms of their value for thedevelopment of veterinary medicine as a branch have been determined.